Syringyl ratio and its relation to the erythro ratio of β-O-4-structure in leaf cell walls. (3rd May 2021) - Xu, Zeming; Nakamura, Hirotaka; Akiyama, Takuya; Yokoyama, Tomoya; Jin, Zhenfu; Sasaki, Kiyokuni; Matsumoto, Yuji
Abstract: In case of wood cell walls, there is a very clear relationship between the aromatic structure of lignin and the stereo configuration of β-O-4-structures; the syringyl ratio (S ratio, syringyl/(syringyl + guaiacyl)) obtained by the nitrobenzene oxidation method is linearly correlated to the erythro ratio (E ratio) of β-O-4 structure ( erythro /( erythro + threo )) obtained by the ozonation method. In this study, 21 leaf samples and 9 stem samples were analyzed to examine whether such relationships can be found in the lignin of leaf and stem cell wall samples. Although some correlation between the S and E ratios was found in leaf and stem cell wall samples, the correlation was not as clear as in the case of woods (correlation coefficient, R 2 = 0.988 for 21woods and R 2 = 0.653 for all the leaf, stem and wood samples). In addition, the E ratios of some leaf samples were lower than 0.5, which is the lowest limit of the E-ratio for wood lignin. It was demonstrated that wood, stem and leaf samples are roughly distinguished by the yield of ozonation and nitrobenzene oxidation products from the sample (not from lignin), but not by the apparent lignin content obtained by the Klason method. The presence of syringyl nuclei in the leaves of Ginkgo, which is classified as gymnosperm, was confirmed by nitrobenzene oxidation.